The cortisol awakening response: More than a measure of HPA axis function - Clow, Angela; Hucklebridge, Frank; Stalder, Tobias; Evans, Phil; Thorn, Lisa (Neuroscience and biobehavioral reviews, 2010)
In most healthy people morning awakening is associated with a burst of cortisol secretion: the cortisol awakening response (CAR). It is argued that the CAR is subject to a range physiological regulatory influences that facilitate this rapid increase in cortisol secretion. Evidence is presented for reduced adrenal sensitivity to rising levels of ACTH in the pre-awakening period, mediated by an extra-pituitary pathway to the adrenal from the suprachiasmatic nucleus (SCN). A role for the hippocampus in this pre-awakening regulation of cortisol secretion is considered. Attainment of consciousness is associated with ‘flip-flop’ switching of regional brain activation, which, it is argued, initiates a combination of processes: (1) activation of the hypothalamic pituitary adrenal (HPA) axis; (2) release of pre-awakening reduced adrenal sensitivity to ACTH; (3) increased post-awakening adrenal sensitivity to ACTH in response to light, mediated by a SCN extra-pituitary pathway. An association between the CAR and the ending of sleep inertia is discussed.